IN VITRO ANTIOXIDANT ACTIVITY OF ETHANOLIC EXTRACT OF BARK OF ALSTONIA SCHOLARIS - Sodhi, Jaspreet Kaur; Kaur, Avneet; Shrivastava, Birendra; Lamba, Hardarshan Singh; Sharma, Jaya; Sharma, Jaya (International Journal of Psychosocial Rehabilitation, 2020)
Alstonia scholaris belonging to family Apocynaceae is commonly known as Devil’s tree or Saptaparni. It is an evergreen tropical tree native to Indian sub-continent and South East Asia. It contains various phytoconstituents like alkaloids, triterpenoids, flavonoids, steroids and phenolic acids which have shown promising therapeutic potential. The present research was subjected to evaluate the in vitro antioxidant activity of ethanolic extract of bark of Alstonia scholaris using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. The extract showed significant antioxidant activity when compared to ascorbic acid. The results of this research work are promising thus indicating the utilisation of the bark of Alstonia scholaris as a significant source of natural antioxidant.